Experimental and theoretical study of constructive and destructive wave interference in a coaxial 1D Bragg structure - McGrane, P; Konoplev, I; Ronald, K; Cross, A; Phelps, A (2004)
A theoretical and experimental study of wave interference in coaxial 1D Bragg structures is presented. Using coupled-wave theory the expression for the wave-coupling coefficient was generalised. The possibility to control the frequency band and mode structure of scattered waves is discussed. It is shown that such control can be achieved by adjusting the relative phase of the ID corrugations on the inner and outer surfaces of a coaxial waveguide with respect to each other. The 1D corrugated coaxial Bragg waveguide was studied using 3D computer simulations and coupled-wave theory. The theoretical results obtained for the basic co-axial model with a single corrugated conductor are compared with experimental measurements. ©2004 IEEE.